Fermi surface traversal resonance in metals: Two theories and an experiment - Ardavan, A; Schrama, J; Blundell, S; Singleton, J; Semeno, A; Goy, P; Kurmoo, M; Day, P (1999)
Fermi-surface traversal resonance (FTR) is caused by the periodic motion of carriers in a magnetic field across open sections of Fermi surface (FS). Owing to the warping of the FS, the real space velocities of the carriers oscillate, generating resonances in the high frequency conductivity which may be described by a semiclassical model. A rectangular resonant cavity, oscillating at 70 GHz, which can rotate in the external magnetic field, has been used to confirm the existence of the effect in the organic metal alpha-(BEDT-TTF)(2)KHg(SCN)(4). The data contain a great deal of information about the FS, including the direction and anharmonicity of warping components. A quantum mechanical model is presented which predicts all of the features of FTR appearing in the semiclassical model. This confirms that FTR is a fundamental property of few-dimensional systems, existing under a very wide range of conditions.